Effectiveness of written emotional disclosure interventions for eating disorders: a systematic review and meta-analysis - Wang, Yufei; Xu, Tao; Tao, Yuexian; Cai, Xintong (Frontiers in Nutrition, 2024)
Background Eating disorders are illnesses that can seriously impair the health and wellbeing of patients. Written emotional disclosure has been recognized as a therapeutic technique that may be helpful in aiding patients’ emotional and psychological adjustment. However, it is unclear what favorable effects eating disorder patients can derive from written emotional disclosure therapy. This study aimed to review the effectiveness of written emotional disclosure in treating eating disorders using a systematic review and meta-analysis. Objective This study was to examine the validity of written emotional disclosure intervention for eating disorders as well as to provide guidelines for the management of eating disorders in patients. Methods Researchers independently developed inclusion and exclusion criteria according to the PICOS principle and systematically searched English literature databases such as PubMed, Medline, Web of Science, Cochrane Library, CINAHL, EBSCO, Embase, and so on, from the time of library construction to December 2023. Cochrane Risk of Bias version 2 (RoB 2) was used to evaluate studies included in this review. All the studies included in this study were randomized controlled trials. Accurate information was extracted and then subjected to meta-analysis with Review Manager 5.4 software. The credibility of the evidence of the studies was assessed using GRADEprofiler 3.6 software. Results The final analysis included 13 randomized controlled trials involving 1,444 participants. The written emotional disclosure intervention can decrease eating disorder symptoms scores (SMD = −0.20, 95% CI [−0.34, −0.05], Z = 2.59, p = 0.01), body dissatisfaction scores (SMD = 0.37, 95% CI [0.21, 0.52], Z = 4.59, p < 0.001), and thin ideal internalization score (SMD = 0.42, 95% CI [0.22, 0.62], Z = 4.12, p < 0.001). Anxiety scores (MD = 0.43, 95% CI [−0.77, 1.63], Z = 0.70, p = 0.48), depression scores (MD = −0.66, 95% CI [−1.78, 0.47], Z = 1.14, p = 0.25) and negative affect scores (SMD = 0.51, 95% CI [−0.24, 1.27], Z = 1.33, p = 0.18), with no statistically significant differences. Conclusion In conclusion, this systematic review analyzed the existing literature and showed that written emotional disclosure intervention is effective in alleviating eating disorder symptoms and patients’ body image problems, but there is insufficient evidence in alleviating depression, anxiety, and negative affect. However, the evidence is limited. Therefore, more research is needed in the future to further enrich the evidence for written emotional disclosure intervention in the field of eating disorders. Systematic review registration https://www.crd.york.ac.uk/prospero/,CRD42023445577.